Pilot Study of Corneal Sensitivity and Its Association in Keratoconus. Issue 2 (February 2017) - Mandathara, Preeji S.; Stapleton, Fiona J.; Kokkinakis, Jim; Willcox, Mark D. P.
Abstract : Purpose: To evaluate corneal sensitivity and its association with other clinical parameters in keratoconus. Methods: Twenty-four subjects with keratoconus aged between 18 and 65 years were recruited in this cross-sectional study. Ocular symptoms, corneal topography, tear variables such as tear osmolarity, volume and lower tear meniscus height, ocular surface staining, central sensitivity threshold (CST), and corneal subepithelial nerve mapping were obtained. Association between central CST and other clinical variables was examined using the Spearman correlation coefficient. Partial correlation was performed to control for effects of confounding factors. Results: Data from the most severe eye of each subject were included in analyses. Based on the maximum simulated keratometry (Kmax) reading, subjects were graded as having mild (N = 11; K max ⩽ 52 D) or severe (N = 13; K max > 52 D) keratoconus. Central corneal sensitivity was lower (ie, increased CST) in the severe keratoconus group compared with that in the mild keratoconus group (median, interquartile range: 1.09; 0.60–19.66 vs. 0.51; 0.39–1.51 g/mm 2, P = 0.035). In bivariate correlations, reduced corneal sensitivity in keratoconus was associated with age ( ρ = 0.42, P = 0.040), disease duration ( ρ = 0.49, P = 0.015) and severity ( ρ = 0.44; P = 0.032), lower central nerve fiber density ( ρ = −0.68, P = 0.014), contact lens wear ( ρ = 0.44; P = 0.025), and contact lens tolerance ( ρ = 0.46; P = 0.033). After adjusting for contact lens wear, reduced corneal sensitivity was negatively associated with ocular symptoms ( ρ = −0.426, P = 0.048) and pain sensitivity ( ρ = −0.423, P = 0.045) and positively associated with corneal staining ( ρ = 0.52, P = 0.011). Conclusions: Altered corneal sensitivity in keratoconus affected ocular symptoms and ocular surface health, which may have significant impact on the success of management options for keratoconus.